Harnessing nature-based solutions for smallholder plant health in a changing climate - Egan, Paul A; Chikoye, David; Green, Kristina Karlsson; Tamò, Manuele; Feit, Benjamin; Kumar, P. Lava; Bandyopadhyay, Ranajit; Tepa-Yotto, Ghislain T.; Ortega-Beltran, Alejandro; Sæthre, May-Guri; Coyne, Danny L.; Legg, James P.; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The impacts of climate change on resource-poor farmers are especially severe and include increased challenges with food security and food safety. This report explores how linking the frameworks of nature-based solutions, integrated pest management (IPM), and One Health can facilitate the design of climate-resilient plant health systems, with particular benefits for reduced pesticide use and exposure. Climate-smart approaches to IPM are proposed as a means to reduce emerging risks from pest insects, nematodes, weeds, and diseases under climate change. We elaborate the main climate change threats – and adaptation options – for five key nature-based solutions central to IPM: host plant resistance and tolerance, habitat manipulation, biological control, semiochemical control, and the use of biopesticides. We conclude by laying out a road map for ‘climate-smart IPM’, which outlines the types of support required for practical implementation, such as climate-informed advisory services, information and communication technology, and policy. While emphasis throughout is placed on smallholder production systems – particularly for sub-Saharan Africa – the principles of climate-smart IPM can be considered relevant to crop production generally.